Eastern Han (AD 25-220) tombs in Sichuan - Chen, X (2014)
This thesis concerns the factors underlying the popularity of the cliff tomb, a local burial form in the Sichuan Basin in China in the Eastern Han dynasty (AD 25-220). The development of the cliff tomb was held in a complex set of connections to the development of the burial forms, and existed through links to many other contemporary burial forms, the brick chamber tomb, the stone chamber tomb, and the princely rock-cut tomb. These connections and links formed to a large extent through the incorporation of the Sichuan area into the empire which began in the fourth century BC. It was in this context, a series of factors contributed to the formation and popularity of the cliff tombs in Sichuan. The hilly topography and the soft sandstone, easy to cut, provided the natural condition for the development of the cliff tombs. The decision to make use of this natural condition was affected by many factors rooted in the social background. The inherent nature of the cliff tomb structure was fully explored, which was then followed by a series of corresponding innovations on the pictorial carvings and the burial objects. The meaning of a continuous family embedded in the cliff tomb structure was explored, as the construction of the tomb was the result of the continuous endeavours from many generations of the family, and the physical form of the cliff tomb was a metaphor for a prosperous family. Following this intention of the tomb occupants underlying the design of the cliff tomb structure, the pictorial carvings and the burial objects in the cliff tomb made adaptations to make the cliff tomb an embodiment of relations between different family members and different generations.